Research on Inter-Regional Population Migration as a Labor Supply Chain - Usenko, Lyudmila; Nasirov, Yuri; Karpenko, Kristina; Mirokhina, Alla; Erdnieva, Elzata (International Journal of Supply Chain Management, 2021)
This article explores the determinants of interregional labour migration in southern Russian regions. Using a basic gravity model with very specialized variables (working-age population, the nearest distance between the administrative regional centres) we partially confirmed hypotheses concerning the presence of a gravitational link between separate regions in southern Russia. The relevance of the topic is determined by the increasing imbalance in the labour force, the partial territorial desertification and the lack of adequate authority measures to regulate migration processes by preserving the integrity of out-migration areas. During the research period (1995-2018), the gravity between regions was both centripetal and centrifugal depending on its centre. In turn, prioritized attraction points are urban settlements within the Southern Federal District. During our regression analysis, we identified four significant variables having the most significant impact on the number of working-age drop-out population: share of the urban population, the average per capita monetary income of the population, length of paved roads, and unemployment rate. The calculations showed the low significance of the GRP level, the number of crimes, the total population and the mortality of the working-age population for migration processes. The prosperous urban territories are gravitated to each other and provide labour resources at the interregional level.